SISTEM PENDETEKSI NILAI PH DAN TEMPERATUR AIR SUMUR DI DAERAH KP RAWA MENGGUNAKAN METODE SAW BERBASIS IOT - Joni Warta; Wowon Priatna; Asep Ramdhani Mahbub; Dwi Budi Srisulistiowati (Fakultas Ilmu Komputer dan Desain - Unsurya, 2023)
AbstractManufacture of a tool using IoT technology that can be used to improve water quality properly and in real-time. The data will be a suitable and inappropriate reference for the quality of the water to be used by the community. Data will be taken from several groundwater samples to evaluate water quality using the Simple Additive Weighting (SAW) method to determine an alternative choice based on predetermined weights and criteria. In the process of designing groundwater temperature and pH detection systems using the IoT-based SAW method with web-based applications, the tools made can be run remotely with a micro device called Wemos D1 R32 as the control center connected to the website and pH and temperature sensors as readers sample data. With this detection tool, you can find out with satisfactory results.Â Keywords: Simple Additive Weighting, Well Water, Internet of Things, Wemos D1 R32.